2017
DOI: 10.1111/febs.14332
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of ER stress in the etiology and pathogenesis of Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized by synaptic dysfunction and accumulation of abnormal aggregates formed by amyloid-β peptides or phosphorylated tau proteins. Accumulating evidence suggests that alterations in the buffering capacity of the proteostasis network are a salient feature of AD. The endoplasmic reticulum (ER) is the main compartment involved in protein folding and secretion and is drastically affected in AD neurons. ER stress triggers the activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
163
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(169 citation statements)
references
References 167 publications
(237 reference statements)
1
163
0
5
Order By: Relevance
“…Neurotoxicity induced by amyloid-β peptides are caused by mitochondrial dysfunction and oxidative stress (18), alteration of metal ion influx (19), endoplasmic reticulum stress (20) and impaired autophagy (21). Amyloid β-induced neuronal cell death may be partially alleviated by antioxidants (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Neurotoxicity induced by amyloid-β peptides are caused by mitochondrial dysfunction and oxidative stress (18), alteration of metal ion influx (19), endoplasmic reticulum stress (20) and impaired autophagy (21). Amyloid β-induced neuronal cell death may be partially alleviated by antioxidants (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…The cause of impaired proteostasis in AD is still unknown although several hypotheses have been proposed. There is convincing evidence that ER stress is increased in human AD brains and might have a causative role in the pathogenesis of AD [61]. In their seminal study, Hoozemans et al [62] demonstrated that the immunohistochemical staining of phosphorylated pPERK (activated) and UPR chaperone BiP/GRP78 were markedly increased in the neurons of temporal cortex and hippocampus in AD patients.…”
Section: Er Stress In Alzheimer's Diseasementioning
confidence: 99%
“…Aβs have been reported to induce apoptosis in neuronal cells by mitochondrial dysfunction and oxidative 2 , and incubated to achieve complete cell attachment. Cells were treated for 4,8,12,48,72 stress (10), alteration of metal ion influx (11), endoplasmic reticulum stress (12) and impaired autophagy (13). In order to test the generality of cell protective activity of SE, we investigated here whether SE protects the neuronal cell death induced by amyloid β-peptides (Aβ and Aβ [25][26][27][28][29][30][31][32][33][34][35] ).…”
Section: Ammonium Hydroxide Results: Se Showed Hormetic Growth Stimumentioning
confidence: 99%